2018
DOI: 10.1111/gec3.12364
|View full text |Cite
|
Sign up to set email alerts
|

Five classes of geospatial data and the barriers to using them

Abstract: Geospatial technologies implemented through the World Wide Web (Geoweb) have improved steadily over the last decade. This Geoweb has the potential to allow citizens to collect and use geospatial data in an effort to influence urban planning in a bottom‐up manner—a stark departure from traditional top‐down public consultation in urban planning. This article reviews five classes of geospatial data available to citizens trying to influence urban planning. These classes have been reviewed in the academic literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Big data can be defined in a variety of ways depending on the disciplines and subjects being studied. However, there are three components that can be considered the fundamentals of big data termed the "three Vs": (1) volume-the quantity of data that are collected, stored, and processed; (2) velocity-how fast the data are collected and processed; and (3) variety-the types/sources of data [38][39][40]. This study aimed to highlight the usefulness of the longest track records of the Atlantic hurricane public database in tandem with multiple geospatial data and hurricane modeling techniques in order to identify the most vulnerable areas to hurricanes in a spatially explicit manner.…”
Section: Modeling Large-scale and Long-term Historical Hurricanesmentioning
confidence: 99%
“…Big data can be defined in a variety of ways depending on the disciplines and subjects being studied. However, there are three components that can be considered the fundamentals of big data termed the "three Vs": (1) volume-the quantity of data that are collected, stored, and processed; (2) velocity-how fast the data are collected and processed; and (3) variety-the types/sources of data [38][39][40]. This study aimed to highlight the usefulness of the longest track records of the Atlantic hurricane public database in tandem with multiple geospatial data and hurricane modeling techniques in order to identify the most vulnerable areas to hurricanes in a spatially explicit manner.…”
Section: Modeling Large-scale and Long-term Historical Hurricanesmentioning
confidence: 99%
“…Previous academics have investigated various aspects that have influenced the use of geospatial technology. Reynard [9] has reviewed past studies on geospatial technologies using the World Wide Web (Geo Web). The results have identified two barrier factors: financial barriers and technological barriers.…”
Section: Literature Review On Factors Influencing Usage Of Geospatial...mentioning
confidence: 99%
“…Among the examples of geospatial technology are Global Positioning System (GPS), Geographic Information Systems (GIS), spectral imagery, Light Detention and Ranging (LiDAR), and aerial photography are examples of geospatial technology [2][3][4][5][6][7]. Although geospatial technology is getting more stable, some obstacles are found to hinder its development; including financial [8,9], lack of knowledge [4], lack of experience [10], lack of training [9], data sharing data is not manageable [11], lack of support from institutional [12], and poor communication among organizations [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that geographic data attracts growing interest from data users, and also the scholars reviewed show that it is valuable to users and therefore should be more open, data authorities nevertheless continue to ignore the potential of geographic initiatives. In a recent study, Reynard (2018) revealed that despite the relevant and significant contributions of a Public Participatory Geographic Information System (PPGIS) developed to work in mobility issues throughout Edmonton (Canada), the city hall ignored its results and took a top-down approach without considering the data generated by citizens and the empirical results that showed where the city infrastructure could be improved.…”
Section: Problemmentioning
confidence: 99%